Neurological uses of cannabis - Pushpendra Nath Renjen; Dinesh Mohan Chaudhari; Anjali Mishra; Abhas Kumar (Apollo Medicine)
Cannabis preparations have been used as medications since the 19th century in Europe and much longer as a traditional medicine in other cultures. The American Academy of Neurology recently published a position statement and concluded that medical marijuana is “probably effective” for some symptoms of multiple sclerosis (spasticity, central pain, painful spasms, and urinary dysfunction), “probably ineffective” for levodopa-induced dyskinesias of Parkinson's disease, and of “unknown efficacy” in nonchorea symptoms of Huntington's disease. This article is focused on review of the medicinal use of cannabis in neurological disorders.